Bacterial Peptidoglycan as a Driver of Chronic Brain Inflammation. Issue 7 (July 2020) - Laman, Jon D.; 't Hart, Bert A.; Power, Christopher; Dziarski, Roman
Abstract : Peptidoglycan (PGN) is a cell wall component of both Gram-positive and Gram-negative bacteria. Signature fragments of PGN are proinflammatory through engagement of pattern recognition receptors (PRR) on resident tissue cells and circulating leukocytes. Despite its abundance in the gut microbiota, there is limited recognition that PGN could contribute to chronic neuroinflammation. This review highlights current insights into the roles of PGN as a determinant of brain inflammation, notably in multiple sclerosis (MS) and its experimental autoimmune encephalomyelitis (EAE) models. Recent studies demonstrate PGN in blood of healthy adult humans. PGN amplifies autoimmune pathology via activation of innate immune cells. Novel uptake routes through (altered) gut mucosa by myeloid leukocyte subsets promote PGN transport to the brain. Highlights: All bacteria require PGN as a major component providing structural rigor. Pattern recognition receptors from several families determine inflammatory versus inhibitory actions of PGN signature fragments. PGN is a determinant in setting innate immune parameters and brain function. In animal models and in tissue from live and postmortem MS brain tissue donors, PGN can be detected in phagocytic cells. In EAE models, PGN promotes inflammation, downstream of NOD receptors. Macrophages, dendritic cells, and neutrophils likely transport PGN from the mucosa to the brain. The clinical implications of PGN as a central element of the gut–brain axis include the development of novel biomarker assays for monitoring of disease activity and treatment, as well as novel interventions involving immunotherapeutics, dietary intervention, and biotics.